2011
DOI: 10.1111/j.1365-2982.2011.01801.x
|View full text |Cite
|
Sign up to set email alerts
|

Myenteric neural network activated by motilin in the stomach of Suncus murinus (house musk shrew)

Abstract: The results indicate that motilin directly stimulates and modulates suncus gastric contraction through cholinergic, adrenergic, serotonergic, opioidergic, and NO neurons in the myenteric plexus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 51 publications
5
29
0
Order By: Relevance
“…From in vivo and in vitro experiments using S. murinus, we demonstrated that motilin-induced gastric contractions are mediated through the myenteric plexus (Mondal et al 2011;Sakahara et al 2010). Similar results have been reported in other species (De Smet et al 2009;Kitazawa et al 1995;Mizumoto et al 1993;Ohshiro et al 2008;Van Assche et al 1997).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…From in vivo and in vitro experiments using S. murinus, we demonstrated that motilin-induced gastric contractions are mediated through the myenteric plexus (Mondal et al 2011;Sakahara et al 2010). Similar results have been reported in other species (De Smet et al 2009;Kitazawa et al 1995;Mizumoto et al 1993;Ohshiro et al 2008;Van Assche et al 1997).…”
Section: Introductionsupporting
confidence: 86%
“…The response to motilin in the proximal corpus was higher than that in the other parts of the stomach, especially with the low motilin concentration, i.e., the 10 −10 M motilin concentration, which slightly induced contractions and the contraction response at 10 −9 M were significantly higher in the proximal corpus than that in the other parts. We previously published reports of concentration-dependent contractile effects of motilin on the isolated S. murinus whole stomach in vitro, and there reported that motilin-induced contraction occurred starting from the 10 −9 M concentration (Mondal et al 2011). Even though the stomach was divided into four sections, each of sections retained the ability to react to motilin, similar to that observed in vitro in the whole stomach.…”
Section: Discussionmentioning
confidence: 55%
“…5). It is noteworthy that motilin began to evoke gastric contraction of S. murinus at 1 nM but was unable to do so at 100 pM in vitro (54). Stomach contractions occurred in response to 100 pM ghrelin after pretreatment with motilin alone, but only small contractions occurred when stomachs were pretreated with [D-Lys-3]-GHRP-6 or G5-1 in conjunction with motilin, even at high doses of ghrelin.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, in contrast to rats and mice, it also expresses motilin (39). However, in the same species it has been shown that motilin induces phase III contractions independently of the vagus nerve via a myenteric cholinergic neural pathway (40,41). It is unclear whether the administration of a low dose of erythromycin is still able to induce a phase III contraction in vagotomized patients.…”
Section: Figurementioning
confidence: 99%